2021
DOI: 10.1371/journal.pcbi.1008835
|View full text |Cite
|
Sign up to set email alerts
|

Choice of method of place cell classification determines the population of cells identified

Abstract: Place cells, spatially responsive hippocampal cells, provide the neural substrate supporting navigation and spatial memory. Historically most studies of these neurons have used electrophysiological recordings from implanted electrodes but optical methods, measuring intracellular calcium, are becoming increasingly common. Several methods have been proposed as a means to identify place cells based on their calcium activity but there is no common standard and it is unclear how reliable different approaches are. H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…Computing statistics for average JS divergence between place fields, percentiles exceeding 0.95 and information score thresholds in range result in statistically lower JS divergence between place fields exclusively identified by SCOUT compared with those identified exclusively by cellReg (min p = 0.0079, max p = 0.0488, linear mixed effects model with fixed cell-tracking method grouped by recording, Figure 6 B). This range of values matches that of a previous study ( Grijseels et al., 2021 ) that suggests a percentile threshold of 0.95–0.99 of place cells, while experimentation showed that neurons with information score threshold exceeding 1.0 showed strong spatially localized firing activity.…”
Section: Resultssupporting
confidence: 90%
“…Computing statistics for average JS divergence between place fields, percentiles exceeding 0.95 and information score thresholds in range result in statistically lower JS divergence between place fields exclusively identified by SCOUT compared with those identified exclusively by cellReg (min p = 0.0079, max p = 0.0488, linear mixed effects model with fixed cell-tracking method grouped by recording, Figure 6 B). This range of values matches that of a previous study ( Grijseels et al., 2021 ) that suggests a percentile threshold of 0.95–0.99 of place cells, while experimentation showed that neurons with information score threshold exceeding 1.0 showed strong spatially localized firing activity.…”
Section: Resultssupporting
confidence: 90%
“…Motion correction of the raw movies, cell detection and signal extraction were performed as previously published using custom MATLAB scripts (Dong et al, 2021). Place fields (PFs) were identified and defined as in Dong et al 2021 using a method combining criteria about the peak fluorescence, stability and size of the PF compared against chance levels (Dombeck et al, 2010; Dong et al, 2021; Grijseels et al, 2021; Sheffield et al, 2017). Note that the criteria previously established were loose enough to not exclude shifting PFs.…”
Section: Data Preprocessingmentioning
confidence: 99%
“…To identify significant place cells, we utilized an approach based on Dombeck et al, 2010 137 (but see also Grijseels et al, 2021 138 for overall caveats with such approaches). Place fields were determined during active trials, indicated by active licking within reward zones, and at running speeds greater than 5cm/s.…”
Section: Discussionmentioning
confidence: 99%